2005
DOI: 10.21061/jcte.v21i2.661
|View full text |Cite
|
Sign up to set email alerts
|

The Perceived Influence of Industry-Sponsored Credentials on the Recruitment Process in the Information Technology Industry: Employer and Employee Perspectives

Abstract: The increase in the number of industry-sponsored credential programs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 29 publications
2
20
0
Order By: Relevance
“…Sweeney and Bame-Aldred (n.d.) show that in a sample of around 1000 new hires in the accounting field 27% had some type of professional certification. According to Barlett et al (2005) around one third of surveyed employees in IT industries had an industry certification.…”
Section: The Significance Of Certificationsmentioning
confidence: 99%
“…Sweeney and Bame-Aldred (n.d.) show that in a sample of around 1000 new hires in the accounting field 27% had some type of professional certification. According to Barlett et al (2005) around one third of surveyed employees in IT industries had an industry certification.…”
Section: The Significance Of Certificationsmentioning
confidence: 99%
“…A vendor that successfully introduces their curriculum into a classroom benefits by gaining an allegiance of trained workers to support their product, service, or technology (Computer Science and Telecommunication Board, 2001). Bartlett (2002) indicated that IT certifications may act to satisfy not only the training needs to support the products and services of a company, but they also act to increase a vendor's market share and revenue. Students working with a particular vendor's software, hardware, and proprietary curriculum over a period of time may develop a prefer-ence for a particular product and ultimately promote that brand of technology out in the workforce.…”
Section: Who Benefits?mentioning
confidence: 99%
“…The position that an individual obtains when attempting to enter IT workforce is limited by the amount of previous work experience in IT and the amount of formal education acquired. The lack of formal education limits the range of career opportunities, and secondary students entering the IT workforce without further formal education may find that their employment is short-lived with limited career opportunities (Bartlett, 2002).Since many of the certification programs are narrowly focused on a particular product or technical specialty, there are many considerations that need to be taken into account so as to influence IT curriculum development in a positive way. According to the U.S. Department of Commerce (2003), educational institutions using IT certification programs as a substantial part of their IT curriculum may not be able to respond to new skill demands when the IT industry changes.…”
mentioning
confidence: 99%
“…A response within these courses has been to include industry-based training and industry liaison within and along side existing tertiary IT courses. It seems that IT courses and industry training are seen to be particularly conducive to using these approaches (Bartlett, 2002;Flynn, 2001;McCain, 2001;Filipczak, 2000).…”
Section: Government Demands On Tertiary Institutionsmentioning
confidence: 99%